Mapping: Ways of representing the world - Dorling, D; Fairbairn, D (Routledge, 1997)
Illustrates how maps tell us as much about the people and the powers which create them, as about the places they show. Presents historical and contemporary evidence of how the human urge to describe, understand and control the world is presented through the medium of mapping, together with the individual and environmental constraints of the creator of the map.